PENERAPAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION TERHADAP HASIL BELAJAR SISWA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL KELAS VII SMP - Adinda Tasya Salsabilah; Luvy Sylviana Zanthy; Sriyatun Sriyatun (IKIP Siliwangi, 2023)
The purpose of this research is to explain the improvement of mathematics learning outcomes for grade VII students at SMP Negeri 2 Cimahi with the “Realistic Mathematical Education approach”. This research method is classroom action research. The subject of this research is 15 students from VII grades. The device used in this research is an essay test with 4 questions. The test is used to reveal students' mathematics learning outcomes. As a data analysis of student mathematics learning outcomes in the first cycle are students who have completed (33%) and students have not completed (67%), while in cycle II students who have completed become (73%) and have not completed (27%) the average value the class increased in the first cycle = 58 while the class average value in the second cycle = 79 which significantly increased, thus according to the results of the data analysis obtained, it was concluded that through the Realistic Mathematical Education Learning approach, students were able to improve mathematics learning outcomes in class X software engineering.